The Psychological Impact of Global Education Approach to SDGs. A Study on Emotions and Sustainability Attitudes of European Teachers - Boffi, Marco; Rainisio, Nicola; Inghilleri, Paolo (Frontiers in Psychology, 2022)
In line with the international policies, Global Education (GE) programs have been widely spread in European schools over the last twenty years, in order to promote environmental and social sustainability and the achievement of the Sustainable Development Goals. Despite this popularity, their effects on attitudes and behaviors have been poorly investigated so far, particularly for teachers. Our study addressed this research gap analyzing the psychological impact of an extensive GE project involving 1303 teachers from 10 European countries. Relevant changes in teachers’ emotional states and attitudes towards sustainability and migrations were analyzed through a pre-post experimental design. Results showed that the GE activities had wide positive effects on teachers, reducing their negative emotions during teaching, increasing their attitudes about sustainability, and mitigating negative attitudes towards migrants. No significant impacts on positive emotions have been detected. Educational and methodological implications of the applied psychological assessment are finally discussed.